2018
DOI: 10.1002/adfm.201803946
|View full text |Cite
|
Sign up to set email alerts
|

Constructing a “Native” Oxyfluoride Layer on Fluoride Particles for Enhanced Upconversion Luminescence

Abstract: The efficiency and tenability of upconversion fluorescence are correlated closely to the structure of host materials. Herein, an oxyfluoride layer grown in situ on fluoride-based upconversion crystals through a hightemperature air annealing is employed to synthesize stable lattice-mismatch NaYF 4 :Yb 3+ /Er 3+ @YOF:Yb 3+ /Er 3+ core/shell architecture with greatly enhanced upconversion luminescence. Such a "native" oxyfluoride layer suppresses the surface quenching and modulates the phonon energy of host mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…The reason for luminescence enhancement of the core‐shell heterostructures are complex, and it could be attributed to the multiple effects including the improved crystal quality, passivated surface effect by oxide shell, and improved energy transfer efficiency through the synergistic effect of fluoride and oxide phonons. [ 16 ] Output color can be also intentionally tuned by varying the contents of Tm 3+ ions in a three‐component dopant system (NaYF 4 :Yb 3+ /Er 3+ /Tm 3+ @YOF:Yb 3+ /Er 3+ /Tm 3+ ) based on the control of relative ratio of dual emission process. [ 23 ] As shown in Commission International de l'Eclairage (CIE) chromaticity coordinates, the samples after LI exhibit a wider tuning range from green via yellow to crimson (Figure 5B).…”
Section: Resultsmentioning
confidence: 99%
“…The reason for luminescence enhancement of the core‐shell heterostructures are complex, and it could be attributed to the multiple effects including the improved crystal quality, passivated surface effect by oxide shell, and improved energy transfer efficiency through the synergistic effect of fluoride and oxide phonons. [ 16 ] Output color can be also intentionally tuned by varying the contents of Tm 3+ ions in a three‐component dopant system (NaYF 4 :Yb 3+ /Er 3+ /Tm 3+ @YOF:Yb 3+ /Er 3+ /Tm 3+ ) based on the control of relative ratio of dual emission process. [ 23 ] As shown in Commission International de l'Eclairage (CIE) chromaticity coordinates, the samples after LI exhibit a wider tuning range from green via yellow to crimson (Figure 5B).…”
Section: Resultsmentioning
confidence: 99%
“…Liang et al 6 designed a highly efficient β-NaYF 4 :Er 3+ ,Yb 3+ @SiO 2 @TiO 2 UC material as a scattering layer and achieved a PCE of 9.21%. Tian et al 7 also reported that incorporation of the core−shell NaY-F 4 :Yb 3+ ,Er 3+ @YOF:Yb 3+ ,Er 3+ UC phosphor resulted an improved DSSC efficiency from 7.02 to 8.39%. Also, the DC phosphor in photovoltaic application is reported to provide an excellent photo-physical and light harvesting feature.…”
Section: ■ Introductionmentioning
confidence: 98%
“…Lanthanide ion doped upconversion nanomaterials (LUNMs) have received tremendous attention in recent years owning to their unique photophysical characteristics and wide application spanning from solid state lasers, photovoltaic conversion, 3D display, bioimaging, photoinduced therapy, to temperature sensor techniques. The upconversion luminescence efficiency and purity of emission color are vitally important for practical application. Until now, numerous efforts have been conducted to improve luminescence performances, such as inert shell coating, , laser sensitization, , dopant distribution optimization, and host matric selecting .…”
Section: Introductionmentioning
confidence: 99%